2020
DOI: 10.3390/ijms21072429
|View full text |Cite
|
Sign up to set email alerts
|

CBD Reverts the Mesenchymal Invasive Phenotype of Breast Cancer Cells Induced by the Inflammatory Cytokine IL-1β

Abstract: Cannabidiol (CBD) has been used to treat a variety of cancers and inflammatory conditions with controversial results. In previous work, we have shown that breast cancer MCF-7 cells, selected by their response to inflammatory IL-1β cytokine, acquire a malignant phenotype (6D cells) through an epithelial–mesenchymal transition (EMT). We evaluated CBD as a potential inhibitor of this transition and inducer of reversion to a non-invasive phenotype. It decreased 6D cell viability, downregulating expression of recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 30 publications
(49 reference statements)
0
43
0
Order By: Relevance
“…Treatment of 6D breast cancer cells with CBD was able to significantly reduce migration and invasion, promoted the recovery of cell contacts, and reduced the expression of malignant markers. CBD was also able to increase sensitivity to anticancer agents doxorubicin and cisplatin in 6D cells by down-regulating the expression of resistance proteins [98]. In murine models of breast cancer, CBD reduced cell proliferation and overall tumour growth, as well as migration and invasion to reduce metastasis [97].…”
Section: Breast Cancermentioning
confidence: 98%
“…Treatment of 6D breast cancer cells with CBD was able to significantly reduce migration and invasion, promoted the recovery of cell contacts, and reduced the expression of malignant markers. CBD was also able to increase sensitivity to anticancer agents doxorubicin and cisplatin in 6D cells by down-regulating the expression of resistance proteins [98]. In murine models of breast cancer, CBD reduced cell proliferation and overall tumour growth, as well as migration and invasion to reduce metastasis [97].…”
Section: Breast Cancermentioning
confidence: 98%
“…We note that the use of cannabidiol (CBD), which reduces Id1 transcription, has been reported to inhibit aggressive breast cancer cell behavior as a single agent 67 . This may in part reflect broad CBD activity against a variety of factors including β-catenin and protein kinase B (AKT) among others 68 .…”
Section: Discussionmentioning
confidence: 99%
“…CBD reduced the proliferation rate at higher CBD concentrations in all breast cancer cell lines, but not in the normal breast cells. It was reported that the viability of MCF7 cells at a specific concentration of CBD (10 μM) was reduced to 90% by CBD and this occurred through interaction with the CB1 receptor [ 19 ]. Although it is known that the relationship between CB receptors and the anti-cancer effect of CBD has been uncertain, it was reported that CBD downregulated the CB1 receptor level through the low expression of CNR1 and could reduce the viability of MCF7 cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBD also downregulated the expression of EMT markers such as Slug and Vimentin. CBD might cause breast cancer cells to be less aggressive by mesenchymal reversion to an epithelial phenotype via IL-1β/IL-1R/β-catenin, E-cadherin/β-catenin complex relocalization, and other protein markers of malignancy [ 19 ]. Thus, it could be understood that CBD can inhibit the aggressiveness of breast cancer and be sensitized to more aggressive breast cancer cells by regulating a variety of signaling pathways and immunologic factors related to malignancy as well as Src/VHL/HIF-1α signaling.…”
Section: Discussionmentioning
confidence: 99%